VALUE CHAIN ANALYSIS: BUSINESS MODEL, OPERATION, AND FINANCE MANAGEMENT OF CAPTURE FISHERIES BUSINESS - wibowo, martino; Anwar, Kasful; Mubarok, Faizul; Khurniawan, Arie Wibowo; Wongsuwatt, Sippavitch (Indonesian Fisheries Research Journal, 2024)
This study analyzes the value chain in small and medium-sized fishery enterprises across several Indonesian provinces (Jakarta, Yogyakarta, Bali, South Sulawesi, and West Sumatra). To fully comprehend the value chain in the fishing industry, it is essential to answer the research problems of the pattern identification of the capture fish value chain, and the implementation of the business process in the capture fish industry. It identifies challenges and opportunities within the value chain, particularly regarding resource access, regulation, transportation, and financial impacts. The research employs a comprehensive value chain analysis, utilizing the Business Model Canvas approach. Primary and secondary data were gathered through interviews and analyzing external data sources. It was done from May to November 2023 involving 50 seafood restaurant owners and 110 fishermen in five provinces. The analysis was conducted using panel data methods with robustness tests performed to ensure the validity of the results The study finds significant operational challenges in maintaining the quality and quantity of fresh fish, inefficiencies in various stages of the value chain, and potential areas for improvement in the captured fisheries business models of SMEs and the big firm. It highlights the importance of market stability, sustainable practices, and economic viability for the growth of SMEs in the fishery sector.